COMPLEX NETWORK-BASED COMPLEX ENVIRONMENT MODEL FOR AUTONOMOUS VEHICLE, AND COMPLEX NETWORK-BASED COGNITIVE SYSTEM FOR AUTONOMOUS VEHICLE AND COGNITION METHOD OF COMPLEX NETWORK-BASED COGNITIVE SYSTEM - SUN, Xiaodong; XIONG, Xiaoxia; WANG, Hai; CAI, Yingfeng; TENG, Chenglong; LIU, Qingchao (2022)
A complex network-based complex environment model for an autonomous vehicle, a complex network-based cognitive system for an autonomous vehicle and a cognition method of a complex network-based cognitive system. On the basis of sensing the external environment of an autonomous vehicle, for a complexity problem of individual driving behavior cognition, driving style recognition is performed by using driving feature parameters which are used for representing a degree of aggressiveness of a driving operation, and a mode transfer preference; on the basis of a complex network, a time-variable dynamic complex network is established according to crowd behavior features of moving subjects in the environment and by taking the moving subjects as nodes and roads as constraints, and the time-variable dynamic complex network is taken as a complex environment model for the autonomous vehicle; the nodes in the complex environment model are subjected to parameterization expression so as to realize differentiated cognition fo